UJI EFEKTIVITAS PERBANDINGAN BAHAN KOMPOS PAITAN (Tithonia diversifolia), TUMBUHAN PAKU (Dryopteris filixmas), DAN KOTORAN KAMBING TERHADAP SERAPAN N TANAMAN JAGUNG PADA INCEPTISOL - Aminah Arifiati; S Syekhfani; Yulia Nuraini (Jurnal Tanah dan Sumberdaya Lahan, 2017)
Inceptisol is one of new developing land which is widespread in Indonesia, with the content of N is relatively low. An increase in the utilization of the content Inceptisol nutrient as agricultural land needed. Compost is organic material which decomposed by microorganisms decomposing, so it can be utilized by plants. The manufacture of compost affect the nutrient compost content. Three basic composting chosen materials are: 1) Paitan, Ferns, and Goat manure. The purpose of this study are: 1) Determine the N content in compost difference material composition ratio of Paitan, Ferns and Goat Dung. 2) Determine the effectiveness of N uptake of maize on the difference material composition compost ratio in Inceptisol. The study was conducted with 5 treatments 3 replications namely: TK0 (control), TK1 (soil + 171 g poly-1), TK2 (soil + 326 g poly-1), TK3 (330 g poly-1), and TK4 (328 g polybag-1).The research results showed that the highest N content by composting material composition of Paitan, Plant Spikes and goat manure in the 1: 2: 3 ratio (K1) with 2.99% of N total. Application of compost to the material composition ratio 3: 1: 2 (K3) showed the highest influence on the total soil N-beginning and end of 0.27% at 0 HST and 0.31% at 60 HST. Compost K3 also provides the most excellent effect on N uptake by plant uptake value of 12.9 g-1. And affect the growth of plants as well as high-Organic C content in analytical beginning nor end